Reports from the Field: COLLABORATING WITH TEACHERS IN THE SELECTION OF TEACHER EDUCATION CANDIDATES: ONE EXPERIENCE - Duquette, Cheryll (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1993)
In recent years faculties of education in the province of Ontario have been inundated with applications for admission. One faculty has responded by giving more careful attention to its criteria for admission and its selection procedures. In this paper is described the collaborative work of the University of Ottawa and the Ontario Teachers Federation in the development of the criteria and selection procedures of applicants to a B.Ed. program. RÉSUMÉ Depuis quelques années, les facultés des sciences de l'éducation de l'Ontario sont littéralement submergées de demandes d'admission. L'une d'entre elles a réagi en réexaminant attentivement ses critères d'admission et ses modalités de sélection. L'auteur de cet article décrit la collaboration qui s'est instaurée entre l'Université d' Ottawa et la Fédération des enseignants et enseignantes de l'Ontario pour fixer les critères et les modalités de sélection des candidats à un programme de B.Ed.